PROSES PERADILAN TINDAK PIDANA KESUSILAAN YANG DILAKUKAN ANAK DI BAWAH UMUR DI PENGADILAN NEGERI MARISA KABUPATEN POHUWATO - Muh. Nasir (AkMen JURNAL ILMIAH, 2013)
The research was conducted in the jurisdiction of the District Court in the District Pohuwato Marisa precisely in the District Court in the District Pohuwato Marisa. The method used in this paper with a qualitative method of data collection techniques were interviews and documentation, and data collected in the analysis with descriptive techniques. Based on the results of the study showed that the factors underlying the occurrence of a crime committed decency minors among other external factors consisting of the environmental factors, the family, the economy, the government. Criminal justice process for children conducted in accordance with the rule of law Juvenile Court No. 3 of 1997 and how to prevent it is to create a harmonious family environment and the provision of education more towards morality, and how menaggulangi namely through parental control on child behavior and more intennya law enforcement officials in cases of crimes committed minors.